Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/app.35452
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of poly(ethylene terephthalate‐co‐isophthalate) during solid state polymerization

Abstract: Poly(ethylene terephthalate-co-isophthalate) (PETI) prepolymer was submitted to solid state polymerization (SSP) at 184-230 C in a fixed bed reactor, to study the evolution of morphological changes during the process. Short reaction times were selected to investigate crystallization phenomena during nonisothermal (heating) and isothermal SSP phases. More specifically, multiple PETI melting behavior was observed and attributed to secondary crystallization, the rate of which increased significantly with SSP temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
2
10
0
1
Order By: Relevance
“…The existence of two crystallization events for PEF and the absence of crystallization events during the heating process for PETc (as observed by Vouyiouka et al) and PET is an evidence that PEF presents a higher tendency to crystallize than PET, as confirmed by XRD. However, analyzing the DSC results for the polyesters, summarized in Table , it is possible to observe that the variation in the enthalpy recorded during the melting process for the PEF resin is lower than both PET and PETc, which could contradict the other experimental data and indicate that PEF is less crystalline.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The existence of two crystallization events for PEF and the absence of crystallization events during the heating process for PETc (as observed by Vouyiouka et al) and PET is an evidence that PEF presents a higher tendency to crystallize than PET, as confirmed by XRD. However, analyzing the DSC results for the polyesters, summarized in Table , it is possible to observe that the variation in the enthalpy recorded during the melting process for the PEF resin is lower than both PET and PETc, which could contradict the other experimental data and indicate that PEF is less crystalline.…”
Section: Resultssupporting
confidence: 55%
“…The fact that PEF melts at lower temperatures than PET may constitute an intrinsic advantage of PEF, since less energy may be required for processing. However, the lower thermal stability and the higher degree of crystallinity of the furanic polyester demands a more efficient control of the processing temperature in order to avoid both degradation and nucleation during processing …”
Section: Resultsmentioning
confidence: 99%
“…Despite that, significant fluctuations can be observed in the t‐ charts built to monitor crystallinity in Year02 and the F‐ charts built to monitor the acetaldehyde concentration in Year03. It is interesting to observe that heated nitrogen is used simultaneously to promote the PET crystallisation and to remove volatile byproducts, which can explain why the control charts are usually similar for crystallinity and acetaldehyde concentration. As the control of crystallinity and acetaldehyde concentration are more stable than control of the IV, it seems reasonable to assume that these variables are subject to distinct perturbations at plant site.…”
Section: Espc Application and Discussionmentioning
confidence: 99%
“…As one can see in Figure , the distribution of measured acetaldehyde concentrations is narrow and the process is able to keep this output variable within the specification limits. It is also important to emphasise that it is well known that acetaldehyde averages and variances are reduced at PET solid state polymerisation plants because of the carrier gas effect.…”
Section: Espc Application and Discussionmentioning
confidence: 99%
“…Vouyiouka et al studied the morphological changes of PET prepolymer during SSP. They concluded that secondary crystals are strongly dependent on the SSP temperature [1] . Commercial PET was exposed to ethylene diamine vapors in order to reduce its molecular weight.…”
Section: Introductionmentioning
confidence: 99%